Molecular Targets and Therapeutic Strategies in Spinocerebellar Ataxia Type 7 - Niewiadomska-Cimicka, Anna (Neurotherapeutics, 2019)
Spinocerebellar ataxia type 7 (SCA7) is a rare autosomal dominant neurodegenerative disorder characterized by progressive neuronal loss in the cerebellum, brainstem, and retina, leading to cerebellar ataxia and blindness as major symptoms. SCA7 is due to the expansion of a CAG triplet repeat that is translated into a polyglutamine tract in ATXN7. Larger SCA7 expansions are associated with earlier onset of symptoms and more severe and rapid disease progression. Here, we summarize the pathological and genetic aspects of SCA7, compile the current knowledge about ATXN7 functions, and then focus on recent advances in understanding the pathogenesis and in developing biomarkers and therapeutic strategies. ATXN7 is a bona fide subunit of the multiprotein SAGA complex, a transcriptional coactivator harboring chromatin remodeling activities, and plays a role in the differentiation of photoreceptors and Purkinje neurons, two highly vulnerable neuronal cell types in SCA7. Polyglutamine expansion in ATXN7 causes its misfolding and intranuclear accumulation, leading to changes in interactions with native partners and/or partners sequestration in insoluble nuclear inclusions. Studies of cellular and animal models of SCA7 have been crucial to unveil pathomechanistic aspects of the disease, including gene deregulation, mitochondrial and metabolic dysfunctions, cell and non-cell autonomous protein toxicity, loss of neuronal identity, and cell death mechanisms. However, a better understanding of the principal molecular mechanisms by which mutant ATXN7 elicits neurotoxicity, and how interconnected pathogenic cascades lead to neurodegeneration is needed for the development of effective therapies. At present, therapeutic strategies using nucleic acid-based molecules to silence mutant ATXN7 gene expression are under development for SCA7. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13311-019-00778-5) contains supplementary material, which is available to authorized users.